Short Communication: Preharvest drought stress varies grain physical characteristics, milling percentage, and nutritional quality of two Job’s tears varieties (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Wicaksono FY, Suganda TW, Wuminta, Sinniah UR, Yuwariah Y, Nurmala T. 2022. Short Communication: Preharvest drought stress varies grain physical characteristics, milling percentage, and nutritional quality of two Job’s tears varieties. Biodiversitas 23: 1443-1448. Preharvest drought stress is one of the limiting factors that may affect the quality of the harvested yield. This study aimed to evaluate the grain physical characteristics, milling percentage, and nutritional quality of two varieties of Job’s tears (Coix lacryma-jobi L.) in response to preharvest drought stress. Two varieties of Job’s tears were used in the present study, namely ma-yuen (cultivar Watani Wado)and stenocarpa (cultivar Watani Kiara Payung) at Ciparanje research station (6.9164° S, 107.7717° E) from July 2018 (dry season) to January 2019 (rainy season). A water-sufficient condition was achieved by irrigating the plant once a day, while a water-deficient condition was formed by the irrigation every 3 days using a sprinkler system. The results showed that preharvest drought stress caused a significant reduction of seed size in both varieties. However, the stenocarpa was the only one with a significant reduction in milling yield due to its long seed length. In terms of nutritional quality, ma-yuen showed no significant response to preharvest drought, while stenocarpa showeda significant gain in protein and calcium. This finding opened the high potential of stenocarpa variety to be used both as an ornament, just like recent usage, and also functional food.